PERMASALAHAN PENGATURAN TENTANG PENGUSAHAAN SARANG BURUNG WALET ALAMI DI KABUPATEN KUTAI KARTANEGARA - Ricky Saputra R (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTRicky Saputra. R, NPM: 13.11.1001.1011.222, " Conflicts Regulations Exploitation of swallow nest naturally Between Local Regulation No. 2 of 2015 and Customary Law in Kutai regency ". Supervised by Mrs. Isnawati, SH, M.H and Mr. Drawan Hasyim, SH, M.Si. The Formulation Issues discussed the author is about how exactly the provisions of the rules regarding the harvest of natural swallow's nests of the nicest and How management rights to the discovery of a natural swallow's nests. Type of legal research used in this study is a normative legal research, a study that studied any legal materials relating to the setting time of bird's nest habitat. This study is an analysis coperatif, by comparing the norms of customary law developed in the community with positive legal norms in this respect local regulations and procurement management is pleased with the bird nest. Some of the legislation relied upon in the management and exploitation of bird nest in essence can be expressed as follows, (first) Act No. 5 of 1990 on the conservation of natural resources and ecosystems, (second) Act No. 10 of 2008 on the Environmental Management, (third) Local Regulation No. 2 of 2015  concerning the business license management and operation of bird's nest. Based on the results at the end of Article 19 Regional Regulation No. 2 of 2015 does not apply textually but more contextual, so that subsequent use or enforced in reality is the harvest of two (2) times a year as applicable under local customary law. In connection with the management rights to the discovery of bird's nest, it is necessary that the government or officials associated more careful attention to the evidence early discovery owned by indigenous peoples around the location of the discovery of the cave swallow nest, and immediately granted / issued a certificate on the invention.